Forgiveness and Emotional Well-Being: A Study of Parents of Children with Autism Spectrum Disorders - Fortien, Wulan Stefania; Kusumiati, Ratriana Yuliastuti Endang (Guidance and Counseling Study Program, Pattimura University, 2024)
This study investigates the relationship between forgiveness and subjective well-being among parents of children with autism spectrum disorders (ASD). Using a quantitative correlational approach, the research aims to determine whether forgiveness significantly impacts the subjective well-being of these parents. The study involved 43 participants from SLBN 1 Palangka Raya, who completed questionnaires measuring forgiveness (Heartland Forgiveness Scale) and subjective well-being (SAPAN and SWLS scales). Descriptive statistics revealed high levels of forgiveness and subjective well-being among participants. However, Pearson correlation analysis indicated no significant relationship between the two variables. This suggests that while parents exhibit high forgiveness, it does not necessarily translate to increased life satisfaction or emotional balance. Subjective well-being is influenced by multiple factors, including gratitude, personality, self-esteem, spirituality, and social support. The study highlights the need for further research to explore these additional factors and address limitations such as incomplete samples and participant confusion during data collection. These insights are crucial for supporting the psychological well-being of parents with children who have special needs.